Você viaja e recomenda? Boca a boca eletrônico no mercado de pacotes turísticos: fatores, atitude e a intenção de compra - Farias, Flávia Fernandes (2018)
The electronic word-of-mouth (eWOM) recommendation has been a theme explored by many researchers, mainly due to the rapid growth of Internet use and increased online shopping (Sparks & Browning, 2011). In this context, this research presents a new theoretical model with the general objective of analyzing the factors of the online reviews that explain the attitude with eWOM and its relationship with purchase intention. This model also investigates the relationship between perceived value, attitude with eWOM and purchase intention. The transportation into the narrative is also highlighted in this study. The model was tested by an online survey, with a probabilistic sample composed by 536 consumers. The research data was analyzed by the Structural Equation Modeling (SEM) using the software SmartPLS. The results identified a moderation of the perceived value between attitude with eWOM and purchase intention. It was found that the credibility of the source has a high effect on the perceived quality of the information and the transport to the narrative. The research is exclusively considering the tourism package sector; recommending further studies in other sectors, with different audiences to expand the understanding of the relation among the constructs.